Kebijakan Trans Pakuan Bogor - Utami, Hanna; Arianto; Sulistiawan, Dani Putra; Rohmah, Tri Ainun; Yakin, Muhammad Ainul; Kurniawan, Irfan Arif (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
One of the transportation options in the city of Bogor is the Trans Pakuan Bus, sometimes referred to as the Ragit Transit Bus. It began operations on June 3, 2007, travels 14 kilometers in roughly 45 minutes, and serves the Baranangsiang Bubulak corridor. This line has 16 stops total. Instead of using dedicated lanes, this city bus operates Type 34 buses. The term "literature review" refers to a group of tasks or actions associated with library data collection techniques, such as gathering and organizing sources used in earlier studies. The implementation of the Trans Pakuan Bogor Bus policy is discussed in this study utilizing a research measurement tool made up of six indicators. These indicators include the scope and goals of the policy, available resources, the traits of agents and implementers, the attitudes of implementers, the organizational communication between implementer activities, and the external social, economic, and political conditions. Keywords : trans pakuan bogor, transportation.